Use of isotopically labeled substrates reveals kinetic differences between human and bacterial serine palmitoyltransferase - Harrison, PJ; Gable, K; Somashekarappa, N; Kelly, V; Clarke, DJ; Naismith, JH; Dunn, TM; Campopiano, DJ (American Society for Biochemistry and Molecular Biology, 2019)
Isotope labels are frequently used tools to track metabolites through complex biochemical pathways and to discern the mechanisms of enzyme-catalysed reactions. Isotopically-labelled L-serine is often used to monitor the activity of the first enzyme in sphingolipid biosynthesis, serine palmitoyltransferase (SPT) as well as labelling downstream cellular metabolites. Intrigued by the effect that isotope labels may be having on SPT catalysis, we characterised the impact of different L-serine isotopologues on the catalytic activity of recombinant SPT isozymes from humans and the bacterium Sphingomonas paucimobilis. Our data show that S. paucimobilis SPT activity displays a clear isotope effect with [2,3,3-D] L-serine, whereas the human SPT isoform does not. This suggests that whilst both human and S. paucimobilis SPT catalyse the same chemical reaction, there may well be underlying subtle differences in their catalytic mechanisms. Our results suggest that it is that the activating small subunits of human SPT that play a key role in these mechanistic variations. This study also highlight that it is important to consider the type and location of isotope labels on a substrate when they are to be used in in vitro and in vivo studies.